Urinary tract infection in HIV-positive women - Carvalho, Newton Sérgio de; Bertoldi, Beatriz Zaia; Russo, Patricia da Cruz (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Urinary tract infections (UTI) are common in women and can cause systemic repercussions. In pregnant women, for example, the occurrence of UTI or asymptomatic bacteriuria (AB) can lead to premature birth and fetal death. The generalized immune depletion caused by HIV is related to the exacerbation of infections, and may be related to UTI. Objective: The objective of this review was to evaluate the characteristics of UTI in pregnant and non-pregnant HIV-positive women as well as the factors that interfere in its occurrence. Methods: By searching the databases PubMed, Web of Science, Scielo and Lilacs, we selected eleven articles that correlated UTI and HIV infection in women. Results: Our analysis showed that HIV-positive pregnant women have a higher predisposition to UTI than HIV-negative ones. The Viral Load (VL) is directly related to UTI and AB in HIV-positive nonpregnant women. TCD4 lymphocyte levels (TCD4) lower than 200 cells/mL and VL over 10,000 copies/mL are correlated with higher UTI and AB rates in HIV-positive pregnant women. There is a tendency for greater variability of pathogens in HIV-positive women and a predisposition to higher rates of antibiotic resistance in HIV-positive pregnant women. Conclusion: HIV-positive pregnant women have higher predisposition to urinary tract infection and its incidence is correlated with a high viral load and a low TCD4 count.